2015
DOI: 10.1002/jor.23128
|View full text |Cite
|
Sign up to set email alerts
|

Administration duration influences the effects of low‐magnitude, high‐frequency vibration on ovariectomized rat bone

Abstract: Low-magnitude, high-frequency vibration (LMHFV) has been proposed as a non-drug anti-osteoporosis treatment. However, the influence of administration duration on its effect is seldom investigated. In this study, the effect of 16-week LMHFV (0.3 g, 30 Hz, 20 min/day) on the bone mineral densities (BMDs), bone mechanical properties, and cellular responses of osteoporotic and healthy rats was examined by in vivo peripheral quantitative computed tomography (pQCT), fracture tests, cell assays, and mRNA quantificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 54 publications
2
6
0
Order By: Relevance
“…In our study, ovariectomized rats had increased food intake and body weight, which is consistent with previous reports [58, 59]. It has been shown that application of whole- body vibration partly restores body weight in ovariectomized animals [60, 61].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, ovariectomized rats had increased food intake and body weight, which is consistent with previous reports [58, 59]. It has been shown that application of whole- body vibration partly restores body weight in ovariectomized animals [60, 61].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, we found that 0.5 h of iLMHFV can provide optimal results, with longer treatment being less effective. These results were in agreement with previous findings that early exposure to LMHFV can positively modulate osteoporotic bone and osteoblasts; however, the beneficial effects seem to not give a consistent performance over time [39]. We believe that this is because prolonged intermittent vibration could result in similar effect as Intermittent low-magnitude high-frequency vibration promotes osteogenic protein expression and inhibits osteoclastogenic cytokine secretion in osteoblasts sostenuto vibration, which may cause fatigue of cells to mechanical stimuli, leading to desensitization over time.…”
Section: Discussionsupporting
confidence: 92%
“…Li et al [25] found that vibration of 0.25× g , 35 Hz, and 15 min/day for 8 weeks can up-regulate the expression of osteogenesis-related proteins in bone tissues of OVX rats. Qing et al [26] detected that after 8 weeks of vibration at 0.3× g , 30 Hz, and 20 min/day, the deterioration of trabecular bone in OVX rats was ameliorated and the tibia trabecular BMD was significantly increased. However, Brouwers et al [27] used a vibration of 0.3× g , 90 Hz on ovariectomized rats, twice a day for 20 min, 5 days a week for 6 weeks; no changes in structure and strength of tibiae were observed, and the bone structure in rats was still degraded.…”
Section: Discussionmentioning
confidence: 99%